A new species of Pacifides from the Western Pacific Coast and the first fully freshwater species of the maricolan planarian genus Paucumara (Platyhelminthes, Tricladida, Maricola). Issue 5 (4th July 2021) - Li, Ming-Yi; Ma, Xin-Yi; Li, Wei-Xuan; Yang, Ying; Sluys, Ronald; Chen, Jia-Jia; Li, Shuang-Fei; Wang, An-Tai
Abstract : The present paper describes two new Chinese species of maricolan planarians through an integrated approach, including morphological, histological and molecular phylogenetic analyses. One new species forms the third species of the genus Pacifides and represents the first record of this genus from the Western Pacific. Further we document a third, new species of the genus Paucumara that is fully restricted to freshwater habitats, as it occurs on the shores of the Jialing River in Chongqing municipality far into the interior of China. Molecular phylogenetic analyses enabled us to determine, for the first time, the position of the genus Pacifides in the phylogenetic tree of the marine triclads. We also provide information on the feeding and reproduction of the new species of Pacifides. The paper concludes with two speculative scenarios on the evolutionary history that may have led to the present-day far inland occurrence and freshwater ecology of the new species of Paucumara ; one scenario involves tectonic uplift-driven speciation and niche evolution, while the other invokes passive upstream dispersal via the Yangtze River. http://www.zoobank.org/urn:lsid:zoobank.org:act:43AE0799-EF9E-452F-99E5-AEE2271D3EA9 http://www.zoobank.org/urn:lsid:zoobank.org:act:79AD55BC-CAA1-4769-853E-7B11CC6ED1A7